MDAB project: an assessment of the preparatory courses for mathematics in UiTM / Parmjit Singh Aparerar Singh ... [et al.] - Aparerar Singh, Parmjit Singh; Cheong, Tau Han; Md Nasir, Nurul Akmal; Ramly, Mohd Adlan (Research Management Institute, 2015)
Resonating UiTM's truest and purest purpose, the MDAB Programme was established to provide educational opportunities for the qualified poor Malays and the Bumiputeras from rural areas as well as urban areas, whose parents' monthly income is found to be less than RM2,000. Upon the completion of a six-month preparatory course, MDAB students will be offered opportunities to further their education in UiTM diploma programs or enrol for other skills courses depending on their results. Due to its high impact and social transformative nature, the implementation of this program had caused various stakeholders to be waiting anxiously for favourable and fruitful results. The main anticipation from these faithful stakeholders is to witness these selected students completing the MDAB Programme so that they can progress and perhaps further their studies at a diploma, degree or even post graduate level indicating a successful social engineering.